Efektivitas Larvasida Alami Ekstrak Daun Alpukat (Persea americana Mill.) dengan Teknologi Nano terhadap Mortalitas Larva Aedes aegypti L. - Cania Dewi, Rahmawitra; Razak, Abdul; Satria, Rijal; Hilda Putri, Dwi (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
One of the vectors of dengue fever, the Aedes aegypti mosquito, can be controlled by using synthetic chemical mosquito repellents such as 1% abate (temephos). However, the continuous use of abate 1% can cause water pollution and human poisoning. To overcome the side effects of using synthetic larvicides, plant extracts can be used as natural larvicides, one of which is avocado leaf. One of the efforts to increase the content of active ingredients in avocado leaves can be done by using nano bubbles. This study aims to determine the effectiveness of avocado leaf extract (Persea americana Mill.) on the mortality of Aedes aegypti larvae. This study used a completely randomized design (CRD). There are Control+ and Control- and 3 treatments in the form of avocado leaf extract diluted with nanobubble water with concentrations of 5%, 10% and 15%. The test material used in this study was Aedes aegypti instar III mosquito larvae. Observations were made for 48 hours. Data were analyzed by probit analysis to determine LC50 and LT50, One Way ANOVA and Post Hoc BSD test. The results showed significant differences (P < 0.05). The results of probit analysis obtained LC50 is 5.326% and LT50 value is 35 hours. The conclusion of this study is that avocado leaf extract natural larvicide with nano technology is effective on the mortality of Aedes aegypti larvae.